Hubungan Kecerdasan Emosional Dengan Prestasi Belajar Siswa Kelas XI Sekolah Menengah Kejuruan Santa Familia Di Tomohon - Kandoli, Louisa Nicolina (Peneliti.net, 2024)
Vocational education is education that prepares students to be able to work in the particular field they are pursuing. The teacher's overall responsibility in understanding the development of science and technology is applied in learning in vocational high schools. To anticipate this, especially the world of education must prepare itself to face the global market through careful and accurate planning and preparation. The aim of this research is to determine the relationship between emotional intelligence and the learning achievement of class XI students at Santa Familia Vocational High School in Tomohon City. The method used in this research is method The Relationship between Emotional Intelligence and Learning Achievement of Class XI Students at Santa Familia Vocational High School in Tomohon City. The method used is the survey method. This research examines the relationship between research variables, in the sense of looking at the relationship between variables, namely the independent and dependent variables. After the data is obtained and tabulated, validity and reliability testing is carried out using factor analysis, namely by correlating between instrument item scores using Pearson Product Moment correlation and Cronbach's alpha method. The results of calculations through testing between emotional intelligence and student learning achievement show an rxy correlation value of 0.474. In the table with r values, the rxy correlation of 0.474 is in the range of r values ​​0.40 – 0.59, thus it can be stated that the level of relationship between emotional intelligence (X) and student learning achievement (Y) is quite strong. Based on these results, emotional intelligence contributes to its relationship with student learning achievement. The results obtained through a significant test, with a significant value (t count) of 3.953. The results of comparing the calculated t with the t table value at the significance level of 0.05 and dk (n-2) obtained a t table of 2.005. This states that t calculated is greater than t table. From these results, Ha is accepted and Ho is rejected, it can be concluded that there is a significant relationship between emotional intelligence and student learning achievement.